Economic Management in Improving the Financial Quality of Islam - Azriadi Tanjung; Sriayu Aritha Panggabean (Institute of Computer Science (IOCS), 2021)
Muslims are currently left behind in the economic field. This is what then causes various crises that if not immediately sought a solution will cause Muslims to be more backward. The research aims to analyze economic management in improving the financial quality of Muslims. This research uses a library study approach by analyzing various authoritative books and journals. The results of the penelitaina show that Muslims actually have a very large capital in terms of more independent economic development. Muslims have ZISWAF (zakat, infak, sedekah, and waqf) as a form of Islamic doctrinal teachings. The problem only needs good and reliable governance and in this case management science is the most important keyword that must be applied. In addition, it is necessary to empower the community for the sake of improved the quality of human resources that are more effective, especially in managing zakat.